3 - Senegalese Entrepreneurs in the USA and Managerial Decision making: A pilot study - Tidjani, Bassirou (Africa Development, 2007)
The paper looks at the conditions that influence how Senegalese entrepreneurs create and manage their businesses in the US while acquiring income in order to maintain and improve their social status in Senegal. The study uses the grounded theory to look at three cases in the city of Cincinnati. The study found that the creation of small businesses by Senegalese is the result of a process centred on the search for resources and the definition and protection of their business undertakings. This process is characterised by variations which depend on several conditions: owners’ social profile, their management of the Senegalese community as a key stakeholder, their individual perception of the relation be- tween religion and business, their personal understanding of the US reality, and their rejection or acceptance of the African system. This study concludes that Senegalese business owners approach doing business differently, even though they share the same basic culture and the same objective as their fellow mi- grants, which is to return home with an improved social status. However, given the methodology used (grounded theory), the sample and the pilot nature of the study, these conclusions cannot be generalised. The findings suggest that the study of immigrant businesses requires methodologies that are qualitative, in- terpretative and based on what business owners do and how they think.